Peran Pengawasan Dan Punishment Terhadap Kinerja Karyawan Dengan Disiplin Kerja Sebagai Variabel Intervening Pada Bank Perkreditan Rakyat Se-Kabupaten Serang - Salapudin; Muhammad Suparmoko; Uli Wildan Nuryanto (Shofanah Media Berkah, 2023)
This research aims to determine the role of supervision and punishment on employee performance with the work discipline variable as an intervening variable in people's credit banks in Serang Regency. This population is all employees in BPRs in Serang Regency with a total of 105 employees using a saturated sampling technique by making the entire population used as a sample. This analysis tool uses inferential statistical analysis or Partial Least Square (PLS). The results of this research show that the influence of supervision on employee performance has a positive or acceptable influence, there is a significant influence of punishment on employee performance, there is no influence of work discipline on employee performance. , there is a significant influence of supervision on work discipline, there is a significant influence of punishment on work discipline, work discipline can mediate the influence of supervision on employee performance, work discipline can mediate the influence of punishment on employee performance.